Exploration of Student-Athletes Emotion Regulation in Terms of Gender - Andryanna Carey Oktavia; Miftakhul Jannah (Universitas Negeri Surabaya, 2023)
A student athlete in carrying out multiple roles may have a certain burden directed at them which has the potential to cause certain conflicts between roles and emotions that they must overcome so that good emotional regulation skills are needed. This study aims to explore emotional regulation in student athletes in terms of gender. This study used quantitative research methods. Participants were taken using a saturated sample with all populations sampled. The population in this study was 24 students, with a ratio of 10 male students and 14 female students. The emotion regulation instrument in this study used the IERQ4S emotion regulation scale. Data analysis techniques use descriptive analysis. Results showed that there were differences in emotion regulation between male student athletes and female students. Overall, the results showed that male student athletes had higher grade point averages. The higher the score obtained, the better the emotion regulation. Thus, male student athletes are better able to manage their emotions than female student athletes.